(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the clinical characteristics of pregnant women up to 7 weeks pregnant at Thai Nguyen University of Medicine and Pharmacy Hospital and evaluate the results of medical abortion in the above group of subjects. Subjects: 120 pregnant women with unwanted pregnancies up to 7 weeks (≤ 49 days) who voluntarily terminated their pregnancies by medical abortion at Thai Nguyen University of Medicine and Pharmacy Hospital from June 1, 2023 to June 31, 2024. Materials and methods: Descriptive. Results: The average age was 31.44 ± 6.76 years old, 16 students (13.3%), 18.4% of pregnant women were unmarried, the main reason for abortion was having enough children (62.5%), the distribution of gestational age at 5 weeks, 6 weeks and 7 weeks was 60.8%, 23.3% and 15.9% respectively. The overall success rate was 94.2%, the success rate in the group with a history of abortion was only 82.3%, the average duration of vaginal bleeding was 9.44 ± 3.21 days, side effects were abdominal pain (95%), nausea (25.8%), chills (14.2%), fatigue (12.5%), vomiting (6.7%) and fever (3.3%). 90.8% of customers were satisfied with the medical abortion method. Conclusion: Medical abortion is a safe and effective method for terminating pregnancies up to 7 weeks of gestation, however, caution should be exercised in cases with a history of abortion.